2018
DOI: 10.1287/mnsc.2017.2738
|View full text |Cite
|
Sign up to set email alerts
|

Incentives in Contests with Heterogeneous Solvers

Abstract: In a contest in which solvers with heterogeneous expertise exert effort to develop solutions, a recent paper (Terwiesch, C., Y. Xu. 2008. Innovation contests, open innovation and multiagent problem solving. Management Science. 54( 9) 1529-1543) argues that as more solvers enter the contest, every solver will reduce effort due to a lower probability of winning the contest. This paper corrects mistakes in this theory, and shows that there exist high-expertise solvers who may raise their effort in response to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 8 publications
1
53
0
Order By: Relevance
“…This is the standard approach to analyzing an award scheme in the extant literature (Moldovanu and Sela 2001, Kalra and Shi 2001, Terwiesch and Xu 2008. Ales et al (2016) and Korpeoglu and Cho (2015) further study when it is optimal for the organizer to have an open tournament with free entry or to restrict entry under the WTA scheme. In a free-entry open tournament which allows all agents who wish to participate to do so, N corresponds to a pool of agents who can potentially participate in the tournament.…”
Section: Resultsmentioning
confidence: 99%
“…This is the standard approach to analyzing an award scheme in the extant literature (Moldovanu and Sela 2001, Kalra and Shi 2001, Terwiesch and Xu 2008. Ales et al (2016) and Korpeoglu and Cho (2015) further study when it is optimal for the organizer to have an open tournament with free entry or to restrict entry under the WTA scheme. In a free-entry open tournament which allows all agents who wish to participate to do so, N corresponds to a pool of agents who can potentially participate in the tournament.…”
Section: Resultsmentioning
confidence: 99%
“…This is because in the presence of a large number of solvers in a contest, generally solvers put in less effort, which dominates the diversity effect. Boudreau et al (2016) examined empirically and Körpeoğlu and Cho (2017) examined theoretically the impact of solver heterogeneity and showed that solvers can react differently to more intense competition.…”
Section: Crowdsourcingmentioning
confidence: 99%
“…• Ideation. Recently, a sizable number of studies have sought to understand innovation tournaments Xu 2008, Terwiesch andUlrich 2009) as processes that enable more open and collaborative innovation ecosystems (Körpeoglu and Cho 2017, Wooten and Ulrich 2017, Mihm and Schlapp 2018. Although several questions remain unanswered, the capacity to collect data from such ideation processes offers a unique opportunity to study the evolution of ideas and paradigms/styles (Chan et al 2017) and the role of feedback as well as the implications of different processes and incentives on the creative output.…”
Section: Observations For the Futurementioning
confidence: 99%